Relationship between oral condition and psychomotor development in children aged 6 and 7 years - Rossmary Janelle Navarro Betetta; Guido Alberto Perona Miguel de Priego (Editorial Ciencias Médicas, 2022)
Introduction: Oral health is a current problem in society; preventive measures such as brushing techniques must be according to motor skills. Objective: Evaluate the relationship between oral conditions and psychomotor development in children aged 6 and 7 years. Methods: The sample consisted of 30 children in the age range of 6 and 7 years, who attend "Manuel Bonilla" school (Lima, Peru). It was divided by 2 groups, which were taught two brushing techniques: Bass-modified technique and Fones technique. There were obtained values of oral conditions, according to the levels of gingival index, hygiene index and the level of severity. On the other hand, the levels of psychomotricity were acquired, evaluated by the Bruininks-Oseretsky test. The analysis of the statistical data was executed with the SPSS and R program. Results: A group of 29 children were incorporated into the sample and a total of 631 teeth were analyzed. The results demonstrated a positive association with a single range (gingival bleeding index) of oral conditions and psychomotor aspects of children between 6 and 7 years. Additionally, a positive association was found between the Bass Modifica brushing technique and optimal oral conditions. Conclusions: The current results suggest a marginal association between the variables studied, which may be potentially more significant with an increase in the sample number. As humans develop new motor skills, they should have a better command of basic health needs such as weighing good oral hygiene. Therefore, it is necessary to recommend brushing techniques according to the level of psychomotor development of the child.